PEMBELAJARAN PERSPEKTIF AL GHAZALI DAN IBNU MISKAWAIH - Abdul Halim (Piwulang: Jurnal Pendidikan Agama Islam, 2019)
Human as educational beings (homo educandum) has never been separated from the process of education. Therefore, they can be an object or subject of education. the educational process carried out by humans will coincide with the learning process. learning is the process of interaction between individuals (students) and other individuals (teachers) or with their environment that is intended to change a person's behavior permanently both intellectual, emotional or spiritual aspect through experience. Generally,  theories of learning are behaviorist, cognitive and humanistic theory  that lead to self's change through their learning experience based on purpose. According to Ghazali and Ibn Miskawaih's perspective, the purpose of learning is a positive moral change towards what is done by a teacher.  al Ghazali points that parent is a first educator in the individual life. According to Ibnu Miskawaih, materials for the learning is developed by using Islam epistemology.  and the other hand, al Ghazali declare a material of learning is developed by sufistic values  approach.Manusia mempunyai julukan sebagai homo educanum. Hal ini nampak pada proses kehidupan manusia dimana ia tidak akan pernah lepas dari proses pendidikan. Disatu sisi ia dapat menjadi obyek sekaligus subyek pendidikan. Pembelajaran adalah proses interaksi yang dilakukan oleh peserta didik dan guru atau lingkungannya yang ditujukan untuk merubah perilaku seseorang secara permanen baik aspek intelektual, emosi atau spiritual melalui pengalaman. Pada umumnya teori belajar behaviorisme, kognitif dan humanistik menginginkan adanya perubahan pada diri seseorang sesuai dengan yang ditujukan melalui pengalaman belajarnya. Dalam perspektif tasawuf sebagaimana diungkapkan oleh al Ghazali dan Ibnu Miskawaih bahwa tujuan pembelajaran adalah perubahan akhlak (perilaku) seseorang kepada yang baik yang dilakukan oleh seorang guru dimana menurut pandangan tasawuf bahwa pendidik pertama tersebut adalah orang tua sedangkan materi yang digunakan adalah materi-materi yang secara epistimologis dibangun secara islami sedangkan menurut al Ghazali materi tersebut juga perlu dibangun dengan pendekatan nilai sufistik.